Ulcerated atheroma plaques carotid bifurcation and cerebral embolism - Abó, Juan Carlos (Cirugía del Uruguay, 1971)
Arteriographic, surgical and fundus oculi findings in 32 patients with transitory ischemic brain attacks were analyze.d in order to determine pathogenic mechanisms. In 25 cases these findings confirm or strongly suggest that symptoms were due to microembolisms originated in ateromatous lesions in the carotid bifurcation. In all cases in which arteriography diagnosed ulcerated ateroma plates, this fact was confirmed by surgery. In 5 patients in which only wrinkled ateroma plates were diagnosed, surgery showed that these were ulcerated. Out of 11 patients with ocular symptoms, ipsilateral to the operated carotid lesion, the fundus oculi of 10 showed the existence of microembolism of the retina, mainly of the type of cholesterinic embolism. Three patients of this series presented completely smooth and severely stenosed ateroma plates, which suggests that in these cases te pathogenic mechanism was a reduction of the blood supply to the brain. We can therefore come to the conclusion that in the case of these patients with transitory ischemic brain accidents and ateromatous lesions in the carotid bifurcation, the most frequent pathogenic mechanism by far was microembolisms originated in these lesions. Brain and visual symptoms ceased in all patients who underwent carotid endarterectomy, thus suggesting that this type of lesion requires surgical treatment.